Organ Preservation for Advanced Resectable Cancer of the Base of Tongue and Hypopharynx: A Southwest Oncology Group Trial - Susan G. Urba; James Moon; P.G. Shankar Giri; David J. Adelstein; Ehab Y. Hanna; George H. Yoo; Michael LeBlanc; John F. Ensley; David E. Schuller (2004)
The Southwest Oncology Group designed a phase II trial for patients with base of tongue or hypopharyngeal cancer to evaluate the complete histologic response rate at the primary site after induction chemotherapy followed by chemoradiotherapy for responders. Secondary end points were the rate of organ preservation and the need for salvage surgery.Fifty-nine eligible patients were enrolled; 37 had base of tongue cancer, and 22 had hypopharynx cancer. Forty-two percent had stage III disease, and 58% had stage IV disease. Induction chemotherapy was two cycles of cisplatin 100 mg/m(2) and fluorouracil 1,000 mg/m(2)/d for 5 days. Patients who had a greater than 50% response at the primary site were treated with radiation 72Gy and concurrent cisplatin 100 mg/m(2) for three cycles. Patients with less than partial response at the primary had immediate salvage surgery.Forty-five patients (76%) had a greater than 50% response at the primary after induction chemotherapy; 43 went on to receive definitive chemoradiotherapy. Thirty-two patients (54%) achieved a histologic complete response at the primary site, and an additional nine patients had a complete clinical response, but biopsy was not done. Seventy-five percent of patients did not require surgery at the primary tumor site. The 3-year overall survival was 64%. The 3-year progression-free survival with organ preservation was 52%.Patients with base of tongue or hypopharyngeal cancer treated with this regimen of induction chemotherapy followed by definitive chemoradiotherapy have a good rate of organ preservation without compromise of survival.